Two Manx conversations (1948 and 1952) - Broderick, George (Journal of Celtic linguistics, 2020)
This article contains editions and translations of two recordings of conversations between native Manx speakers from 1948 and 1952 respectively, with detailed linguistic discussion.
Gesehen am 21.08.2024